Pressure‐dependent changes in haematocrit and plasma volume during anaesthesia, a randomised clinical trial. Issue 5 (21st January 2016) - Damén, T.; Reinsfelt, B.; Redfors, B.; Nygren, A.
Abstract : Background: Induction of general anaesthesia has been shown to cause haemodilution and an increase in plasma volume. The aim of this study was to evaluate whether prevention of hypotension during anaesthesia induction could avoid haemodilution. Methods: Twenty‐four cardiac surgery patients, 66 ± 10 years, were randomised to receive either norepinephrine in a dose needed to maintain mean arterial blood pressure (MAP) at pre‐anaesthesia levels after induction or to a control group that received vasopressor if MAP decreased below 60 mmHg. No fluids were infused. Changes in plasma volume were calculated with standard formula: 100 × (Hctpre /Hctpost  − 1)/(1 − Hctpre ). Arterial blood gas was analysed every 10 minutes and non‐invasive continuous haemoglobin (SpHb) was continuously measured. Results: Pre‐anaesthesia MAP was 98 ± 7 mmHg. Ten minutes after anaesthesia induction, the haematocrit decreased by 5.0 ± 2.5% in the control group compared with 1.2 ± 1.4% in the intervention group, which corresponds to increases in plasma volume by 310 ml and 85 ml respectively. MAP decreased to 69 ± 15 mmHg compared to 92 ± 10 mmHg in the intervention group. The difference maintained throughout the 70 min intervention period. The change in haemoglobin level measured by blood gas analysis could not be detected by SpHb measurement. The mean bias between the SpHb and blood gas haemoglobin was 15 g/l. Conclusion: During anaesthesia induction, haematocrit decreases and plasma volume increases early and parallel to a decrease in blood pressure. This autotransfusion is blunted when blood pressure is maintained at pre‐induction levels with norepinephrine.